2018
DOI: 10.1186/s12893-018-0417-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node ratio is inferior to pN-stage in predicting outcome in colon cancer patients with high numbers of analyzed lymph nodes

Abstract: BackgroundThe lymph node ratio (LNR), i.e. the number of positive lymph nodes (LN) divided by the total number of analyzed LN, has been described as a strong outcome predictor in node-positive colon cancer patients. However, most published analyses are constrained by relatively low numbers of analyzed LN. Therefore, the objective of the present study was to evaluate the prognostic impact of LNR in colon cancer patients with high numbers of analyzed LN.MethodsOne hundred sixty-six colon cancer patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Some studies state that LNR is a significant risk factor that should be incorporated into the TNM staging system of the American Joint Committee on Cancer due to its high predictive value for survival [ 39 , 40 ]. However, some studies disagree with this because the lymph node assessment in CRC specimens can be influenced by both surgical and pathological factors, including the extent of the lymph node dissection, the length of the surgical specimen, the surgeon’s technique, and the thoroughness of the pathologists [ 41 , 42 , 43 ]. In our study, the mean number of total harvested lymph nodes was over 20, which is a proxy for high-quality surgical resection [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies state that LNR is a significant risk factor that should be incorporated into the TNM staging system of the American Joint Committee on Cancer due to its high predictive value for survival [ 39 , 40 ]. However, some studies disagree with this because the lymph node assessment in CRC specimens can be influenced by both surgical and pathological factors, including the extent of the lymph node dissection, the length of the surgical specimen, the surgeon’s technique, and the thoroughness of the pathologists [ 41 , 42 , 43 ]. In our study, the mean number of total harvested lymph nodes was over 20, which is a proxy for high-quality surgical resection [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancers are some of the most common forms of cancer, and surgery is the main treatment in most colon cancers. 4 The number of lymph nodes removed during surgery and the number of metastatic lymph nodes affects prognosis and treatment indication. 9 Patients’ lymph node numbers were evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines state that 12 lymph nodes are sufficient for the assessment of lymph node involvement. 3 , 4 However, insufficient lymph node removal can lead to pN-related problems and to difficulties in determining prognosis and treatment planning. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Lymph nodes ratio is considered as an effective parameter for stratification, especially because it seems to be independent of the resection length[ 24 ], and as a strong predictor for tumor recurrence[ 25 , 26 ]. However, the more recent paper of Jakob et al [ 27 ] reported the bigger impact of pN than lymph node ratio on recurrence suggesting that the latter parameter could be more helpful in presence of a relatively low number of harvested lymph nodes[ 27 ].…”
Section: Discussionmentioning
confidence: 99%